WOMEN-WRITERS IN ENGLISH LITERATURE - Erkinov Adham Anvar o'g'li (TADQIQOTLAR.UZ, 2024)
The Second World War was a significant event that left a lasting impact on American society and culture. This article explores the depiction of the war in American literature, examining how writers have grappled with themes of conflict, trauma, and loss. Through an analysis of key works from the period, this article aims to shed light on the ways in which the war has been portrayed in literary texts and its enduring influence on the American literary landscape.